The relationship between school heads’ transformational and structural leadership styles towards teachers’ teaching motivation / Mohd Asraf M Mohd Siraj ... [et al.] - M Mohd Siraj, Mohd Asraf; Md Rami, Ahmad Aizuddin; Abdul Aziz, Nor Azni; Mohd Anuar, Mohd Ashraff (Universiti Teknologi MARA, 2022)
Leadership is crucial in an organisation’s long-term viability and incredibly motivating teachers. Theoretical and conceptual searches for leadership styles that work in any situation, such as teachers’ teaching motivation and with any set of followers, have never been more abundant in the field of leadership research. However, some findings reported that there had been some uncertainty about the relationship of leadership styles towards teacher teaching motivation in some schools. Hence, this study is designed to get the response of primary school teachers in Sabah on the school heads’ transformational and structural leadership styles, the level of teachers’ teaching motivation, and the relationship between the school heads’ transformational and structural leadership styles towards teachers’ teaching motivation. This study is a descriptive quantitative study conducted through a survey using a questionnaire from the instruments of L. Bolman Personnel correspondents for structural leadership style, MLQ (Multi-Factor Leadership Questionnaire) for transformational leadership style, and A Questionnaire Measure of Individual Differences in Achieving Tendency (QMAT) for teaching motivation. The study involved 350 respondents from primary schools in Sabah. The analysis of the findings uses frequency, percentage, mean, standard deviation, and Pearson correlation analysis with determination = 0.05. The results showed that teachers’ response in primary school in Sabah to the leadership style of the school heads is at a satisfactory level. The study also found a significant relationship between the school heads’ leadership styles towards teachers’ teaching motivation. This study supports the findings of other studies, whereby the headmaster leadership styles influence teachers’ level of teaching motivation in schools.